Implementasi PAI dalam konsep kurikulum integrative-implementatif untuk memperkuat dimensi profil pelajar pancasila - Mujahid Damopolii; Nur Ainiyah (Al-Ulum, 2022)
This study aims to describe the contribution of Islamic Religious Education (PAI) subjects in realizing the dimensions of the Pancasila student profile as an essential part of the goals to be achieved in the independent curriculum. This research is qualitative, with data collection techniques, namely literature study. Data is obtained by analyzing books, articles, notes, and various reports related to the problem. Data analysis techniques were carried out using critical analysis techniques. This study shows a correlation and a real contribution to PAI learning in realizing the dimensions of the Pancasila student profile. This can be seen from the objectives of the PAI subject, namely to create students who have a noble character which is reflected in their obedience to worship Allah SWT and daily behavior, maintaining relationships with others, and the surrounding natural environment in synergy with the dimensions of the Pancasila student profile. This synergy means that the success of PAI learning will also significantly impact the success of realizing the Pancasila student profile as one of the strategic plans of the Ministry of Education and Culture for 2020-2024.